High‐flow nasal cannula oxygen therapy for respiratory management after postoperative re‐intubation/re‐extubation in patients with trisomy 18 and trisomy 13: Two case reports. Issue 3 (15th March 2023) - Hirano, Hirofumi; Taniguchi, Yoshie; Kato, Masato
Abstract: We present two cases of general anesthesia in children with 18, 13 trisomy. One patient had difficulty with intubation and had to be reintubated postoperatively, another developed postoperative acute respiratory distress syndrome. The use of postoperative high‐flow nasal cannula oxygen therapy to avoid reintubation is considered a feasible strategy. Abstract : Graphical Abstract The use of high‐flow nasal cannula oxygen therapy for respiratory disorders in children with severe mental and physical disabilities in the perioperative period is applicable to prevent re‐intubation and additional invasive procedures